First identification of nosema ceranae (Microsporidia) infecting apis mellifera in Venezuela - Porrini, Leonardo Pablo (2017)
Nosema ceranae is a pathogen of Apis mellifera, which seems to have jumped from its original host Asiatic honey bee Apis ceranae. Nosemosis which affects the honey bee Apis mellifera is caused by two parasitic fungi described as etiologic agents of the disease. Nosema apis was the only microsporidian infection identified in A. mellifera until N. ceranae in Taiwan and Europe. Nosema spp. positive samples of adult worker bees from the Venezuelean state of Lara were determined through light microscopy of spores. Samples were then tested to determine Nosema species (N.apis/N.ceranae) using previously reported PCR primers for the 16S rRNA gene. A multiplex PCR assay was used to differentiate both N. apis and N. ceranae species. Only N. ceranae was found in the analyzed samples and the percentage of infected foragers fluctuated between 18% and 60%.